Mitochondrial Impairment and Oxidative Stress Are Essential Mechanisms Involved in the Pathogenesis of Acute Kidney Injury (Journal of Renal and Hepatic Disorders, 2023)
Acute kidney injury (AKI) is an emergency condition that requires restrictive and appropriate clinical interventions. Identifying mechanisms of organ injury is a critical step in developing clinical interventions. Unilateral ureter obstruction (UUO) is widely used as an animal model for investigating AKI. The current study was designed to evaluate the role of mitochondrial impairment and oxidative stress in the pathogenesis of renal injury in UUO model. Mice underwent UUO surgery. Then, kidney tissue histopathological changes, plasma biomarkers of renal injury, oxidative stress, and different renal mitochondrial indices were evaluated at scheduled time intervals (3, 7, 14, and 21 days after UUO surgical procedure). Significant increase in plasma creatinine and blood urea nitrogen levels was evident in UUO mice. The UUO surgery induced severe kidney tissue histopathological alterations, including necrosis, severe tubular atrophy, and interstitial inflammation. Moreover, kidney biomarkers of oxidative stress included reactive oxygen species formation, lipid peroxidation, protein carbonylation, decreased glutathione reservoirs (GSH), and increased oxidized glutathione (GSSG) observed in UUO mice. On the other hand, significant mitochondrial depolarization, decreased mitochondrial dehydrogenases activity, mitochondrial permeabilization, and decreased adenosine triphosphate and GSH/GSSG levels were discovered in mitochondria isolated from the kidneys of UUO mice. The data obtained from the current study demonstrated a pivotal and interconnected role for oxidative stress and mitochondrial dysfunction in the pathogenesis of renal injury in UUO model. Therefore, these directions could serve as therapeutic targets in animal models or patients of acute renal failure.
Keywords: antioxidants; bioenergetics; mitochondria; nephrotoxicity; renal failure